1997
DOI: 10.1097/00005344-199712000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Ecto-5′-Nucleotidase Mediates Infarct Size-Limiting Effect by Ischemic Preconditioning in the Rabbit Heart

Abstract: We examined whether ecto-5'-nucleotidase mediates infarct limitation by ischemic preconditioning in the rabbit heart. Ecto-5'-nucleotidase activity in ischemic region after ischemic preconditioning was greater than that in nonischemic regions (23.6 +/- 2.5 vs. 13.6 +/- 1.0 nmol/mg protein/min; p < 0.01). With an inhibitor of 5'-nucleotidase, alpha,beta-methylene adenosine 5'-diphosphate (AMP-CP), ecto-5'-nucleotidase activity in the ischemic region was comparable to that in the nonischemic region. Mean blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Previous studies showed that 5Ј-ND was activated during myocardial ischemia and/or reperfusion and that increased production of adenosine in the myocardial tissue counteracted the cell injury under these circumstances (1,24,25). Inhibition of 5Ј-ND largely increased myocardial infarction induced by a 30-min coronary occlusion and 3-h reperfusion (24). These results support the view that enhanced 5Ј-ND activity protects the tissues or cells from the ischemic injury in the myocardium.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Previous studies showed that 5Ј-ND was activated during myocardial ischemia and/or reperfusion and that increased production of adenosine in the myocardial tissue counteracted the cell injury under these circumstances (1,24,25). Inhibition of 5Ј-ND largely increased myocardial infarction induced by a 30-min coronary occlusion and 3-h reperfusion (24). These results support the view that enhanced 5Ј-ND activity protects the tissues or cells from the ischemic injury in the myocardium.…”
Section: Discussionsupporting
confidence: 77%
“…Given that adenosine can reduce glomerular filtration rate, decrease tubular loading, inhibit tubular ion transport activity, and increase medullary blood perfusion (41,48), this oxidant-induced increase in 5Ј-ND activity or adenosine production may represent an important adaptive mechanism during oxidative stress under pathological conditions such as ischemia and/or reperfusion (1,2,6). Previous studies showed that 5Ј-ND was activated during myocardial ischemia and/or reperfusion and that increased production of adenosine in the myocardial tissue counteracted the cell injury under these circumstances (1,24,25). Inhibition of 5Ј-ND largely increased myocardial infarction induced by a 30-min coronary occlusion and 3-h reperfusion (24).…”
Section: Discussionmentioning
confidence: 99%
“…We further contemplated that our previous observation about elevation of e-AMP level that could not be explained by the unchanged level of ecto-5 0 -nucleotidase app 18 was possibly due to provoked induction of 5 0 -nucleotidase app activity in the blood vessels as already demonstrated in several studies. [50][51][52] In addition, Komamura et al 53 showed that ecto-5 0 -nucleotidase activity in ischemic region of rabbit heart following ischemic preconditioning was greater than that in nonischemic regions. In addition, decrease in ecto-adenosine deaminase app activity raises the level of e-AMP.…”
Section: Discussionmentioning
confidence: 99%
“…After surgery, the preparation was equilibrated for 90 min to allow the stabilization of the interstitial adenosine concentration before the collection of samples was begun. Additional studies were performed to evaluate the effect of the blockade of 5Ј-ND on interstitial adenosine by infusing ␣,␤-mADP at 0.00105 mg ⅐ kg Ϫ1 ⅐ min Ϫ1 into the aorta (6,23). The dose used induced the smaller changes in MAP and urinary flow compared with several tested doses (data not shown), including the 0.035 mg ⅐ kg Ϫ1 ⅐ min Ϫ1 previously described (6).…”
Section: Renal Interstitial Concentration Of Adenosinementioning
confidence: 99%